The Effect of Proposed Training Program in Developing Maximum Speed and Speed Endurance of Basketball Players - Sherwan Saber Khalid; Qahar Ahmed Ali; Ihsandin Othman Abdulla Majidy (University of Basrah, 2023)
Basketball is sport which implies the combination of high-intensity actions with periods of lower intensity and/or recovery. success in elite basketball is mostly determined by fast and power-based sport-specific actions which rely on anaerobic pathways. The aim of the current study is to develop the running ability (maximum speed and speed endurance) of basketball players. The researchers applied experiment method of independent sample with pre and post-tests. (12) participants as the research sample randomly selected from population. They went through a six-week training program consists of speed and speed endurance exercises (individual and group drills). Pre and post tests were applied to determine the effect of the training program on players. The statistical package of social sciences (SPSS) used to analyze the data. The results show that the training program was sufficient to obtain positive effect on speed endurance for basketball players but it was not statistically significant, therefore, the researchers recommended conducting further studies to develop maximum speed of basketball players by utilizing different training methods.